RELEVANCE OF THE USE OF PLANT-BASED INGREDIENTS WITH THE PURPOSE OF REDUCING THE CONTENT OF NITRITE COMPOUNDS IN MEAT PRODUCTS - STEPANOVA, TETIANA; STARYNSKYI, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article presents the results of research on the use of plant ingredients to reduce the content of nitrite compounds in meat products. One of the ways to reduce the content of nitrite compounds in meat products is the inclusion of plant ingredients. One of these is Japanese honeysuckle leaf extract, which has a rich nutrient composition and antibacterial properties. A study was conducted to identify the possibility of using this plant component to reduce the level of nitrite compounds in meat products. Until now, there was not enough information on the use of honeysuckle leaf extract as a preservative for meat products. The presence of compounds with P-vitamin activity in the leaves also determines their antioxidant and anti-inflammatory properties. The role of nitrates and nitrites in the technology of meat products was analyzed, the ways of reducing the content of nitrite compounds in meat products without worsening the quality and safety indicators of the finished product and the feasibility of using an aqueous extract of honeysuckle leaves as a natural preservative for meat products were investigated. The use of an aqueous extract of honeysuckle leaves with an antibacterial purpose is proposed. The use of plant alternative components for use in the composition of meat products was investigated experimentally in order to ensure antimicrobial effect and achieve a preservative effect. It is proposed to use the aqueous extract of Japanese honeysuckle leaves in order to extend the shelf life of the studied products. The possibility of using the aqueous extract of Japanese honeysuckle leaves in the concentration range of 0.1...0.5%, which varies depending on the type of meat products, has been established, which will be the object of further research.